Nanopesticides - Light or dark side of the force? - Marcin Kruszewski; Lucyna Kapka-Skrzypczak (Nofer Institute of Occupational Medicine, 2017)
Nanotechnology has been used in many branches of industry, including agriculture, where nanomaterials are used as carriers of chemical plant protection compounds, as well as active ingredients. Meanwhile, the effects of nanopesticides exposure on the human body are unknown. Due to their occupation, farmers should be particularly monitored. This paper summarizes the use of nanoparticles in agriculture, the route of potential exposure for agricultural workers and the current state of knowledge of nanopesticides toxicity to mammalian cells. The authors also discuss techniques for detecting nanoparticles in the workplace, as well as biomarkers and effects of exposure. The results of this review indicate that the use of nanotechnology in agriculture can bring measurable benefits by reducing the amount of chemicals used for plant protection. However, there is no research available to determine whether or not the use of pesticide nanoformulations increases the harmful effects of pesticides. Moreover, the results of research on cell lines and in animal models suggest that nanoparticles used as active substance are toxic to mammalian cells. Interestingly, there is also a complete lack of epidemiological studies on this subject. In the nearest future the effects of exposure to nanopesticides may require a particular attention paid by scientists and medical doctors who, treat agricultural workers and their families. Med Pr 2017;68(3):423-432